In-Silico Evaluation of Binding Interaction and ADME Properties of Novel Pyrazoline and Pyrimidine Derivatives Targeting Cyclooxygenase-2 Enzyme - Sarmad Abbas Fadhil; Karima Fadhil Ali; Wesen Adel Mehde (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Inflammation is a crucial defense mechanism against toxic stimuli and physical traumas. This study aimed to design six new pyrazoline and pyrimidine derivatives and assess their potential anti-inflammatory activity by targeting the cyclooxygenase (COX) enzyme, a key mediator in the inflammation process. Through in-silico methods, the binding affinity of these derivatives to the COX-2 receptor was predicted using computer simulations and compared with the reference drug, meloxicam.